Perspective Tendencies in Reconstruction of Industrial Building of Central Parts in Modern Cities - O. I. Sysoyeva (Наука и техника)
Industrial buildings of various branches and periods of construction actively participate in so called dialogue of old and up-to-date architecture of the central parts in the cities. Taking into account unprofitability of some productions and requirements to develop the central parts of the cities the paper proposes differentiated approach to the prospects of the reconstruction of industrial building in order to realize the principle of continuity of urban space in time. In accordance with this approach industrial buildings obtain the possibility of continuous renovation and urban environment acquires stability in time and space.